Branching streams flow in the darkness : Zen talks on the Sandokai - Suzuki, Shunryū, 1904-1971 (University of California Press, 1999)
The 'Sandokai', a poem by the 8th-century Zen master Sekito Kisen is the subject of this collection of lectures. Included with the lectures are student questions and Suzuki Roshi's answers, along with a meditation instruction.